2010
DOI: 10.1152/jn.00785.2009
|View full text |Cite
|
Sign up to set email alerts
|

Response Latency to Lingual Taste Stimulation Distinguishes Neuron Types Within the Geniculate Ganglion

Abstract: The purpose of this study was to investigate the role of response latency in discrimination of chemical stimuli by geniculate ganglion neurons in the rat. Accordingly, we recorded single-cell 5-s responses from geniculate ganglion neurons (n = 47) simultaneously with stimulus-evoked summated potentials (electrogustogram; EGG) from the anterior tongue to signal when the stimulus contacted the lingual epithelium. Artificial saliva served as the rinse solution and solvent for all stimuli [(0.5 M sucrose, 0.03-0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
83
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(101 citation statements)
references
References 49 publications
18
83
0
Order By: Relevance
“…This study adds a new layer to the dynamic coding hypothesis, demonstrating that quality-related temporal information is actively shaped by the animal's sampling behavior at the periphery. Although the anatomical segregation and sequential activation of receptive fields during licking likely account for much of the difference seen in reaction times between taste qualities, other sources of peripheral processing, such as transduction cascades and complex synaptic dynamics among taste receptor cells and primary afferent neurons, may also contribute (Breza et al, 2010;Roper, 2013). The results support and add important insights to previous work regarding the role of Figure 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study adds a new layer to the dynamic coding hypothesis, demonstrating that quality-related temporal information is actively shaped by the animal's sampling behavior at the periphery. Although the anatomical segregation and sequential activation of receptive fields during licking likely account for much of the difference seen in reaction times between taste qualities, other sources of peripheral processing, such as transduction cascades and complex synaptic dynamics among taste receptor cells and primary afferent neurons, may also contribute (Breza et al, 2010;Roper, 2013). The results support and add important insights to previous work regarding the role of Figure 9.…”
Section: Discussionmentioning
confidence: 99%
“…As a control for the taste of salt, wild-type mice were initially trained in a salt-detection version of the task in which the no-stop stimulus was water and the stop stimulus was 100 mM NaCl. After reaching Ͼ80% correct performance levels for 3-4 d in a row, these mice were tested in the same task but with 20 M amiloride added to the stimulus solutions to block sodium taste transduction in taste receptor cells (Heck et al, 1984; Hill et al, 1990;Chandrashekar et al, 2010;Oka et al, 2013). Amiloride dropped performance levels in mice to chance levels, demonstrating that mice required the taste of salt to perform the task (Fig.…”
Section: Gustatory Stop-signal Task Is Learned Rapidly and Requires Tmentioning
confidence: 99%
“…Prior studies on peripheral neurons by Marowitz and Halpern (1977) and Breza et al (2010) showed that latency to response to sodium salts inversely followed concentration. The present analysis revealed an inverse relationship between concentration and response latency to sucrose in central neurons, and showed that this relationship was temperature dependent.…”
Section: Temperature and Timingmentioning
confidence: 98%
“…For one, latency was proposed to convey neural information used to represent taste stimuli (Breza et al 2010;Hallock and Di Lorenzo 2006). However, the present data introduce complications for this hypothesis for sucrose.…”
Section: Temperature and Timingmentioning
confidence: 99%
See 1 more Smart Citation